Cognitive and metacognitive learning strategies as correlates of university students’ mathematics proficiency - Polemer M. Cuarto; Enya Marie D. Apostol (International Journal of Evaluation and Research in Education (IJERE), 2026)
Mathematics remains one of the most difficult disciplines in the school curriculum. As such, strategies to address these difficulties are being implemented by educators over the years. This study aimed to determine the influence of the cognitive and metacognitive learning strategies on the mathematics proficiency of university freshmen. Specifically, it sought to assess how students’ use of various cognitive and metacognitive strategies relates to their performance in mathematics. A descriptive-correlational research design was employed to describe the prevailing levels of these learning strategies and examine their association with mathematics proficiency. Data were gathered from 80 randomly selected freshmen students through a validated researcher-made questionnaire and record analysis of their mathematics grades. Results revealed significant positive correlations between control, elaboration, rehearsal, planning, monitoring, and evaluation strategies with mathematics proficiency. The study recommends providing additional mathematics support to struggling students such as remedial and tutorial classes and integrating cognitive and metacognitive learning strategies into the mathematics syllabi. These findings imply that strengthening students’ cognitive and metacognitive awareness can significantly improve their ability to learn and perform in mathematics. Furthermore, integrating these strategies into instructional design may help develop more independent, reflective, and effective learners, leading to higher mathematics achievement.